Integration of Computer Technologies into an English Language Learning Classroom - WANG , Yen-Hui; TSAO , Hsiang-Yun; CHEN , Gaung-Cheng (Asian Journal of Empirical Research, 2013)
The present study integrated computer technologies into regular English classes to examine whether using the online TOEIC simulated-test system could promote the TOEIC listening and reading test performance of a group of Taiwanese EFL learners. The participants involved in the one-academic-year study were 52 second-year Taiwanese technological college students who were required to attend classroom instruction sessions about TOEIC test preparation and online learning sessions during which they had to self-accomplish eight designated practice units of TOEIC simulated tests. Data were collected by two TOEIC simulated-test units serving as the pre-and post-tests to assess participants’ TOEIC test performance in listening and reading comprehension before and after using the online TOEIC simulated-test system. The study results revealed that participants improved with a significant increase in both listening and reading post-test scores, suggesting that learning through the online TOEIC simulated-test system had a facilitating effect on the test performance of the target learners in their listening and reading comprehension.